Pershing's tankers : personal accounts of the AEF Tank Corps in World War I - Kaplan, Lawrence M. (Lawrence Martin), 1954-; Wilson, Dale, 1951- (Lexington, Kentucky : University Press of Kentucky, 2018)
"In Pershing's Tankers, Lawrence M. Kaplan compiles 47 official personal experience reports, 27 unofficial accounts, and six letters written by George Patton to his family to provide insight into the human dimension of US tank operations in World War I. These narratives vary in size, scope and depth, and cover a range of topics, including the organizing, training, combat operations, and equipping of the Tank Corps. Kaplan offers accounts from a broad cross-section of men from senior leaders down to the platoon level"--
Front cover; Copyright page; Contents; Illustrations; Foreword; Editor's Introduction; I Historical Summary of US Army Tank Corps Operations; II Tank Corps Senior Leader Commentary; III Official Tank Corps Personal-Experience Reports; PHOTOGRAPHS; IV Unofficial Personal Accounts; V Unofficial Tank Corps Operational Summaries; Appendix A; Appendix B; Appendix C; Appendix D; Appendix E; Appendix F; Appendix G; Appendix H; Appendix I; Notes; Index
Includes bibliographical references and index.
Online resource; title from digital title page (viewed on August 24, 2018).
JSTOR
Keywords: United States. -- Army. -- Tank Corps -- History; United States. -- Army. -- Tank Corps; World War, 1914-1918 -- Europe -- Personal narratives, American; World War, 1914-1918 -- Europe -- Tank warfare; HISTORY -- Europe -- Western; HISTORY -- Military -- World War I; Tank warfare; Europe; 1914-1918; Electronic books; Personal Narrative; Personal narratives; History; Personal narratives -- American; Personal narratives; Récits personnels